ANDROGENESIS IKAN TAWES (Barbonymus gonionotus Blkr.) dengan IRADIASI UV (λ 254 nm) DAN KEJUT PANAS 40OC - Romdah Romansyah (Algoritma : Jurnal Matematika, Ilmu pengetahuan Alam, Kebumian dan Angkasa, 2024)
This study aims to determine the effectiveness of inactivation treatment of silver barb eggs by UV irradiation for 30 seconds (the dose of 991,67 J/m2) or 50 seconds (the dose of 1652,79 J/m2) for damaging the genetic material of silver barb eggs as assessed by abnormal morphology or appearance of the larvae (or haploid), to determine the effectiveness of diploidization by heat shock at 40°C for 90 seconds to silver barb zygote at 10 or 15 minutes from fertilization time, in order to obtain diploid androgenetic of silver barb as assessed by normal morphological larvae (or diploid) similar to the positive control.Results showed that the average fertility among treatments were highly significant difference.